2009
DOI: 10.1002/path.2661
|View full text |Cite
|
Sign up to set email alerts
|

Nephrin—signature molecule of the glomerular podocyte?

Abstract: In recent years there has been an explosion of interest in the glomerular podocyte, which plays a central role in control of glomerular filtration. A host of new molecules have been identified as playing essential roles in the maintenance of podocyte integrity in both humans and mouse models. Of all of these, arguably the most pivotal is nephrin, a transmembrane receptor molecule located at the specialized podocyte cell-cell junction, termed the slit diaphragm. Mutations in this gene cause the most severe form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 76 publications
4
78
0
2
Order By: Relevance
“…2C). This finding is consistent with early down-regulation of nephrin during disassembly of the slit diaphragm in many cases of glomerular disease without genetic disruption of NPHS1 (14). In contrast, other essential slit diaphragm-associated proteins, such as podocin (27), CD2AP (28), and α-actinin-4 (29) remained unchanged at this time point.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…2C). This finding is consistent with early down-regulation of nephrin during disassembly of the slit diaphragm in many cases of glomerular disease without genetic disruption of NPHS1 (14). In contrast, other essential slit diaphragm-associated proteins, such as podocin (27), CD2AP (28), and α-actinin-4 (29) remained unchanged at this time point.…”
Section: Resultssupporting
confidence: 74%
“…MAGI-2 was also identified in a multiprotein complex in rat kidney glomeruli, where it interacts with nephrin (13), a transmembrane signaling receptor and essential component of the slit diaphragm, a specialized cell-cell junction that prevents urinary protein loss (14,15). The filtration barrier of the kidney is a highly specialized structure, composed of glomerular endothelial cells, glomerular basement membrane, and interdigitating podocyte foot processes bridged by the slit diaphragm protein complex (16).…”
Section: Magi-2/s-scam | Glomerulosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Although acting as an adhesion molecule, nephrin is a pivotal regulator of podocyte intracellular signaling, 26 which is important in downstream Phosphatidylinositide 3-kinase signaling and a negative regulator of nuclear factor-κB activity. TRPC6 interactions with nephrin near the slit diaphragm may underlie regulation of gating and trafficking of these channels and studies have reported that nephrin plays a role in modulating TRPC6 channel opening.…”
Section: Discussionmentioning
confidence: 99%
“…After its discovery, nephrin became a major focus of research efforts around the world and was recently referred to as the signature molecule of the glomerular podocyte. 3 It has been reported that nephrin is a required structural component of the glomerular slit diaphragm; forms a pore structure capable of restricting the passage of albumin-sized molecules; binds numerous other proteins that are both present at the slit diaphragm and required for a proper filtration barrier; and is a lipid raft-associated signaling molecule at the slit diaphragm that undergoes tyrosine phosphorylation and is linked to the actin cytoskeleton within podocyte foot processes. [4][5][6] Although many questions still remain, these results provide important mechanistic insights into the potential roles of nephrin and the slit diaphragm in maintaining podocyte health and in establishing and maintaining a size-selective barrier to albumin.…”
mentioning
confidence: 99%